Identification of Mercury Content in Groundwater at Post-Processing Land for Gold Mining Materials - Mokhram Ari Arbi Ililirugun; Arif Setia Jaya (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
Small-scale gold mining activities in Dava Village still heavily rely on mercury (Hg) in the amalgamation process, potentially contaminating groundwater in the surrounding residential areas. This study aims to analyze mercury concentrations in well water based on nine sampling points representing areas near tailings disposal, amalgam burning locations, and residential zones. Laboratory analysis showed that all samples had Hg concentrations far exceeding national quality standards (<0.001 mg/L), with the highest values found at points S6, S9, and S2, which are close to the pollution source. This spatial pattern indicates a strong relationship between artisanal gold mining activity and increased Hg contamination in shallow aquifers. Environmental factors such as open tailings infiltration, surface runoff, deposition of Hg vapor from amalgam burning, and pH variations also influence mercury mobility and accumulation. This finding confirms that traditional gold processing practices without adequate waste management pose serious risks to public health and environmental quality. Mitigation efforts thru reduced mercury use, better tailings management, and regular water quality monitoring are needed to reduce potential future exposure